Pengaruh Representasi Gender dalam Media Massa terhadap Persepsi Masyarakat tentang Peran Gender - Nugrawan Rusadi, Andi Syahreza; Kamaruddin, Syamsu A; Tenri Awaru, A. Octamaya (Jurnal Tugas Akhir Mahasiswa Pendidikan Sosiologi, 2026)
This study aims to analyze how gender representation in mass media affects public perception of gender roles in social life. This study uses library research the research method is carried out by collecting and analyzing various relevant written sources. These sources can be scientific journals, books, online articles, research reports, or official publications. The results or discussions discussed in this study are: 1) Gender representation; 2) The role of mass media; 3) Gender roles. Why impact because gender representation in mass media has the power to shape people's perspectives on the roles of men and women. This understanding is important so that people are more critical of gender bias and can encourage the creation of equality in social roles